Pengaruh HIIT Tipe II terhadap Optimalisasi Ketahanan pada Pemain Futsal Amatir Muda - Surya Rezeki Sitompul; Ika Yulianingsih; Muhammad Naufal Fajriansyah (Universitas Nusantara PGRI Kediri, 2025)
Surmising non-classroom activities like playing futsal, overall sports competence is largely contingent upon the individual’s physical performance and capacity, particularly their cardiovascular endurance (Vo₂Max) fitness level. For the initial Bleep Test, participants had a rather low average Vo₂Max of 34.9 ml/kg/min. This is explained due to insufficient training periods or volume, inadequate equipment, and unrealistic progression expectations. This study aims to develop motor endurance in students through physical activity. The study uses a pre-experimental design and a single pretest-posttest group design. There were 18 subjects of the study who were active participants in futsal extracurricular activities in the school, aged 15-16 years old. Saturated sampling technique is used to take samples from the entire population. The measurement of Vo₂Max was done using the Bleep Test before and after the exercise intervention to estimate the effectiveness of the program. Type II exercise (HIIT) is proven to have a significant effect. This decision is supported by a t-test value of 15.942, greater than the t-table value of 2.110 at a 5% significance level, and the 0.000 value for significance, which is less than 0.05. Thus, it has been proved that HIIT Type II exercises improve Vo2Max. This study has practical implications as it suggests a workable and quantifiable exercise program to improve adolescent biomotor endurance. This supports the proof that HIIT Type II is an effective exercise method, and it can be incorporated into non-educational school programs as a straightforward way to address the problem of poor aerobic capacity.